Peri‐operative management of an adult with POLG‐related mitochondrial disease. Issue 1 (13th March 2022) - Valent, A.; Delorme, L.; Roland, E.; Lambe, C.; Sarnacki, S.; Cattan, P.; Plaud, B.
Summary: POLG‐related mitochondrial disease is a rare mitochondrial disorder that is potentially associated with anaesthetic complications such as propofol‐related infusion syndrome. A 19‐year‐old man with mitochondrial DNA deletions and POLG‐related disorders presented for an elective robotic Heller‐Dor myotomy for the treatment of oesophageal pseudo‐achalasia associated with severe gastro‐oesophageal reflux. The fasting period was minimised to reduce the risk of metabolic stress. The anaesthetic technique included a rapid sequence induction with propofol and rocuronium, a remifentanil and sevoflurane‐based general anaesthesia with multimodal monitoring and peri‐operative lactate‐free intravenous fluids with added dextrose. The patient did not experience propofol‐related infusion syndrome but did have delayed tracheal extubation due to residual neuromuscular blockade requiring a second dose of sugammadex. This report demonstrates the safety of single‐use, low‐dose propofol in this patient group. Patients with POLG‐related mitochondrial disease may be at risk of prolonged neuromuscular blockade, and appropriate dosing of neuromuscular blocking agents with monitoring of neuromuscular blockade is strongly encouraged.